A generalization of the kinetic equation using the prabhakar-type operators - Dorrego, Gustavo Abel (2017)
Fractional kinetic equations are investigated in order to describe the various phenomena governed by anomalous reaction in dynamical systems with chaotic motion. Many authors have pro- vided solutions of various families of fractional kinetic equations involving special functions. Here, in this paper, we aim at present- ing solutions of certain general families of fractional kinetic equa- tions using Prabhakar-type operators. The idea of present paper is motivated by Tomovski et al.